2013
DOI: 10.1177/0146167212473160
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Multiculturalism

Abstract: We studied the influence of right-wing authoritarianism (RWA) on the relationship between a multicultural ideology and attitudes about ethnic diversity and immigrants. We hypothesized that a multicultural ideology poses a threat to authoritarian individuals, which leads to a decrease in positive diversity beliefs and an increase in prejudice toward immigrants. On the basis of representative survey-data from 23 European countries, we showed that the negative relationship between RWA and positive diversity belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(44 citation statements)
references
References 45 publications
3
32
0
2
Order By: Relevance
“…Firstly, research suggests that the lower the score on RWA the higher openness to diversity (Kauff et al, 2013). Thus, individuals scoring low on RWA may perceive a homogeneous ingroup identity as more unsatisfying than a heterogeneous ingroup identity, and therefore increase outgroup prejudice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, research suggests that the lower the score on RWA the higher openness to diversity (Kauff et al, 2013). Thus, individuals scoring low on RWA may perceive a homogeneous ingroup identity as more unsatisfying than a heterogeneous ingroup identity, and therefore increase outgroup prejudice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, individuals with high scores on RWA value conservatism, authoritarianism and traditionalism (the three sub-dimensions of RWA) to a higher degree in order to preserve ingroup homogeneity and entitativity which is believed to protect the group from potential harm (Altemeyer, 1998;Duckitt, Wagner, du Plessis and Birum, 2002). Additionally, people scoring high on RWA tend to have a more negative perception of diversity in general (Kauff, Asbrock and Wagner, 2013), and hold a strong belief that their surrounding world is generally dangerous and therefore must be controlled (Onraet, Dhont and Van Hiel, 2014). Thus, homogeneous ingroup identities may be perceived as an important resource for individuals scoring high on RWA.…”
mentioning
confidence: 99%
“…One possible explanation for why, in the present study, the effects of the name prime were found only for those participants who were politically conservative is that politically conservative participants may have had low levels of pro-diversity beliefs [17]. By priming those participants with his middle name, it could have served to emphasis the President’s minority status, thereby influencing those participants with lower pro-diversity beliefs to view him more negatively.…”
Section: Resultsmentioning
confidence: 76%
“…Pro-diversity beliefs tend to be related to one’s political ideology. For example, a survey of several European countries showed a negative relationship between right-wing authoritarianism and pro-diversity beliefs [17]. Furthermore, a 2014 poll conducted by the Pew Research Center showed that politically conservative Americans value diversity less than do politically liberal Americans [18].…”
Section: Introductionmentioning
confidence: 99%
“…21], поэтому вера в опасный и вера конку-рентный мир должны быть отрицательно связаны с мультикультурной идеологией. Кроме того, мультикультурная идеология воспринимается как угроза культурным традициям и ценностям людей с высоким АПТ [33]. Само этническое разнообразие представляет угрозу для лиц с высоким АПТ, поскольку это указывает на несо-ответствие групповым нормам и угрозу групповому соответствию [6; 76].…”
Section: настоящее исследованиеunclassified